Relationship of the aromatic structural types in vacuum gas oil to empirical correlations based on bulk properties. (2nd May 2016) - Stratiev, Dicho Stoyanov; Shishkova, Ivelina K.; Nikolaychuk, Ekaterina; Sharafutdinov, Ilshat M.; Vely, Anife; Mitkova, Magdalena; Yordanov, Dobromir; Rudnev, Nikolay
ABSTRACT: Five empirical methods toestimate the content of aromatic, naphthenic, and paraffinic carbon and hydrogen content and the bulk properties were tested for prediction of aromatic structures content of 95 vacuum gas oils. The density demonstrated the highest correlation with the aromatic structures content among all other studied bulk properties and empirical parameters. The aromatic structures content could be predicted by a second order power law dependence on density with accuracy commensurable with the reproducibility of SARA analysis. The poly-nuclear aromatic structures content was also found to depend on the density and can be expressed by a linear function.